Effects of exercise modality on excess postexercise oxygen consumption (EPOC) in female runners - O'Malley, W. L.; Quinn, T. J.; Kertzer, R.; Vroman, N. B. (Medicine & Science in Sports & Exercise, 1997)
This study determined whether female runners (N = 7) elicited the same 3-hour EPOC after a typical run on a treadmill when compared to a non-familiar, air-braked cycle ergometer workout of equivalent relative work level. Ss rested for one hour before being measured for baseline values. That was followed by 45 minutes of exercise at 75% of the randomly selected, mode-specific VO2max. Ss then rested quietly for three hours. Ss performed under both conditions. It was found that physiological familiarity with an exercise modality, in this case running on a treadmill, yielded a lower EPOC than that of the non-familiar cycling task. Implication. Testing for EPOC using activities other than those of the specific-trained sport will yield spurious values. Higher post-exercise metabolic activity results from performing unfamiliar activities. When recovering from exercise or competitions, active metabolisms speed repair and restoration mechanisms. To produce the highest level of post-exercise metabolism it probably would be helpful to perform unfamiliar untrained activities at a low to moderate intensity.